Platelet protein phosphorylation, elevation of cytosolic calcium, and inositol phospholipid breakdown in platelet activation induced by plasmin. - A I Schafer; A K Maas; J A Ware; P C Johnson; S E Rittenhouse; E W Salzman (The Journal of Clinical Investigation, 1986)
Studies have been performed on the biochemical mechanism of platelet activation induced by the fibrinolytic protease plasmin. In washed human platelets, greater than or equal to 1.0 caseinolytic units (CU/ml plasmin induced aggregation. Platelet [14C]serotonin release was stimulated by 1.0 CU/ml plasmin to an extent comparable to that induced by 1.0 U/ml thrombin. A dose- and time-dependent phosphorylation of the platelet 47,000- and 20,000-kD proteins was noted in 32PO4-labeled platelets incubated with plasmin; phosphorylation was not affected by extracellular Ca2+, but was completely inhibited by an increase in platelet cyclic AMP. Phosphorylation of these platelet proteins suggested that plasmin may act on platelets by stimulating a rise in cytosolic calcium concentration ([Cai2+]) and activating inositol phospholipid-dependent phospholipase C and protein kinase C. Using both quin2 fluorescence and aequorin luminescence as indicators, plasmin was found to elevate platelet [Cai2+] in the presence or absence of extracellular Ca2+. Phospholipase C activation was shown by the generation of [3H]diglyceride in [3H]arachidonic acid-labeled platelets and [32P]phosphatidic acid in 32PO4 labeled platelets exposed to plasmin. Plasmin did not induce formation of thromboxane A2 (TXA2). Only small amounts of this eicosanoid were detected late in the time course after plasmin stimulation. Our results indicate that plasmin causes platelet aggregation and secretion associated with phosphorylation of the 47,000- and 20,000-kD proteins, Ca2+ mobilization, and phospholipase C and protein kinase C activation. Images